PENGARUH PERUBAHAN EKOLOGI TERHADAP KESENIAN WAYANG THENGUL NGAWI - Rinta Kharisma; Isa Ansari (Institut Seni Indonesia Surakarta, 2018)
This paper aims to uncover problems about: (1) How the effects of ecological changes on the life of the puppets of Thengul Ngawi and (2) How the effects of ecological changes on the aesthetics of the puppet show Thengul Ngawi. The problems that have been raised are then examined using an ecological and aesthetic approach to puppetry. The existence, life, shape and influence of ecological changes to wayang Thengul which includes the intensity of performances, functions and meanings in the community are examined using the aesthetic concept of populist puppetry. The results of the study that ecological changes occurring in the Ngawi region affect the wayang thengul art. The influence makes it a form of rural-style art belonging to the people of Ngawi, especially in Karangjati District.Keywords: Ecology, Arts, Puppet Thengul.